Design and synthesis of a piperazinylalkylisoxazole library for subtype selective dopamine receptor ligands - Cha, MY; Choi, BC; Kang, KH; Pae, AN; Choi, KI; Cho, YS; Koh, HY; Lee, HY; Jung, D; Kong, JY (PERGAMON-ELSEVIER SCIENCE LTD, 2002)
A piperazinylbutylisoxazole libary was designed, synthesized and screened for the binding affinities to dopamine D-2, D-3, and D-4 receptors. Several ligands were identified to possess high binding affinity and selectivity for the D-3 and D-4 receptors over the D-2 receptor. Compounds 6s and 6t showed K-i values of 2.6 nM and 3.9 nM for the D-3 receptor with 46- and 50-fold selectivity over the D-3 receptor, respectively. (C) 2002 Elsevier Science Ltd. All rights reserved.
Keywords: MOLECULAR-CLONING; HIGH-AFFINITY; D-3 RECEPTOR; ANTAGONIST; GENE; HALOPERIDOL; EFFICACY; AGONIST; CYCLASE; POTENT